АНАЛІЗ ШЛЯХІВ ДОСЯГНЕННЯ ЦІЛЕЙ З 100% ВІДНОВЛЮВАНОЇ ЕНЕРГІЇ У РІЗНИХ КРАЇНАХ СВІТУ - Zheliezna, T.A. (Institute of Engineering Thermophysics of NAS of Ukraine, 2020)
The aim of the work is to analyze targets on the transition to 100% renewable energy sources (RES) existing in different countries of the world as well as strategies for their achievement. The task of the work is to identify the most promising directions and develop appropriate recommendations for Ukraine. The global trend is setting targets for the transition to 100% RES, at least in some energy sectors, developing appropriate strategies and their implementation. Over the last decade, the cost of renewable energy has been steadily declining, making RES more competitive with fossil fuels in many parts of the world. Today, more than 50 countries, hundreds of cities and regions in one form or another have committed to switching to 100% RES. Most often it is about achieving 100% of renewable electricity. So far, at least 52 cities and regions have achieved their targets for the transition to 100% RES. Of these, 41 are located in Europe and 9 are located in the United States. About 2/3 of these targets relate only to renewable electricity. In Ukraine, the official targets for the development of RES are set out in the National Renewable Energy Action Plan until 2020 and in the Energy Strategy of Ukraine until 2035. Recently, a draft Concept of the “green” energy transition of Ukraine until 2050 was developed, which sets the goal of achieving a climate-neutral economy by 2070. One of the main directions of decarbonization of the economy is the development of RES in combination with increasing energy efficiency and energy saving. It is necessary to resume completing the document with the inclusion of reasonable long-term goals to achieve 100% RES in certain energy sectors and in the whole energy balance of Ukraine.